Tisotumab vedotin in patients with advanced or metastatic solid tumours (InnovaTV 201): a first-in-human, multicentre, phase 1–2 trial. Issue 3 (March 2019) - de Bono, Johann S; Concin, Nicole; Hong, David S; Thistlethwaite, Fiona C; Machiels, Jean-Pascal; Arkenau, Hendrik-Tobias; Plummer, Ruth; Jones, Robert Hugh; Nielsen, Dorte; Windfeld, Kristian; Ghatta, Srinivas; Slomovitz, Brian M; et al.
Summary: Background: Tisotumab vedotin is a first-in-human antibody–drug conjugate directed against tissue factor, which is expressed across multiple solid tumour types and is associated with poor clinical outcomes. We aimed to establish the safety, tolerability, pharmacokinetic profile, and antitumour activity of tisotumab vedotin in a mixed population of patients with locally advanced or metastatic (or both) solid tumours known to express tissue factor. Methods: InnovaTV 201 is a phase 1–2, open-label, dose-escalation and dose-expansion study done at 21 centres in the USA and Europe. Patients (aged ≥18 years) had relapsed, advanced, or metastatic cancer of the ovary, cervix, endometrium, bladder, prostate, oesophagus, squamous cell carcinoma of the head and neck or non-small-cell lung cancer; an Eastern Cooperative Oncology Group performance status of 0–1; and had relapsed after or were not eligible to receive the available standard of care. No specific tissue factor expression level was required for inclusion. In the dose-escalation phase, patients were treated with tisotumab vedotin between 0·3 and 2·2 mg/kg intravenously once every 3 weeks in a traditional 3 + 3 design. In the dose-expansion phase, patients were treated at the recommended phase 2 dose. The primary endpoint was the incidence of adverse events, including serious adverse events, infusion-related, treatment-related and those of grade 3 or worse, and study drug-related adverse events, analysed in all patients who received at least one dose of tisotumab vedotin (full analysis population). This trial is registered with ClinicalTrials.gov, number NCT02001623, and is closed to new participants with follow-up ongoing. Findings: Between Dec 9, 2013, and May 18, 2015, 27 eligible patients were enrolled to the dose-escalation phase. Dose-limiting toxicities, including grade 3 type 2 diabetes mellitus, mucositis, and neutropenic fever, were seen at the 2·2 mg/kg dose; therefore, 2·0 mg/kg of tisotumab vedotin intravenously once every 3 weeks was established as the recommended phase 2 dose. Between Oct 8, 2015, and April 26, 2018, 147 eligible patients were enrolled to the dose-expansion phase. The most common (in ≥20% of patients) treatment-emergent adverse events of any grade were epistaxis (102 [69%] of 147 patients), fatigue (82 [56%]), nausea (77 [52%]), alopecia (64 [44%]), conjunctivitis (63 [43%]), decreased appetite (53 [36%]), constipation (52 [35%]), diarrhoea (44 [30%]), vomiting (42 [29%]), peripheral neuropathy (33 [22%]), dry eye (32 [22%]), and abdominal pain (30 [20%]). The most common adverse events of grade 3 or worse were fatigue (14 [10%] of 147 patients), anaemia (eight [5%]), abdominal pain (six [4%]), hypokalaemia (six [4%]), conjunctivitis (five [3%]), hyponatraemia (five [3%]), and vomiting (five [3%]). 67 (46%) of 147 patients had a treatment-emergent serious adverse event. 39 (27%) of 147 patients had a treatment-emergent serious adverse event related to the study drug. Infusion-related reactions occurred in 17 (12%) of 147 patients. Across tumour types, the confirmed proportion of patients who achieved an objective response was 15·6% (95% CI 10·2–22·5; 23 of 147 patients). There were nine deaths across all study phases (three in the dose-escalation phase and six in the dose-expansion phase); only one case of pneumonia in the dose-expansion phase was considered possibly related to study treatment. Interpretations: Tisotumab vedotin has a manageable safety profile with encouraging preliminary antitumour activity across multiple tumour types in heavily pretreated patients. Continued evaluation of tisotumab vedotin is warranted in solid tumours. Funding: Genmab A/S.